The Patient and Carer Race Equality Framework: a model to reduce mental health inequity in England and Wales - Smith, Shubulade Mary; Kheri, Amna; Ariyo, Kevin; Gilbert, Steve; Salla, Anthony; Lingiah, Tony; Taylor, Clare; Edge, Dawn (Frontiers in Psychiatry, 2023)
ABSTRACT The Patient and Carer Race Equality Framework (PCREF) is an Organisational Competence Framework (OCF), recommended by the Independent Review of the Mental Health Act as a means to improve mental health access, experience and outcomes for people from ethnic minority backgrounds, particularly Black people. This is a practical framework that should be co-produced with and tailored to the needs of service users, based on quality improvement and place-based approaches. We aim to use the PCREF to address the longstanding epistemic justices experienced by people with mental health problems, particularly those from minoritised ethnic groups. We will outline the work that led to the proposal, the research on racial inequalities in mental health in the UK, and how the PCREF will build on previous interventions to address these. By taking these into account, the PCREF should support a high minimum standard of mental health care for all. DECLARATION OF INTERESTS Six authors took part in the 2019 Independent Review of the Mental Health Act (1983) African and Caribbean Group (MHARAC): S.G. as co-chair, S.S. as vice-chair, and K.A., A.S., T.L. and D.E. as contributors. D.E. and S.S. are also co-applicants on the the National Institute for Health Research-funded Culturally Adapted Family Intervention (CaFI) study. All other authors declare no competing interests. KEYWORDS Community care; evidence-based practice; health inequalities; health policy; mental health; schizophrenia; service delivery; theoretical articles. FUNDING This research paper was supported by the National Institute for Health Research (NIHR) Health Service and Delivery Research (HS&DR) Programme (project number 12/5001/62), which was awarded to D.E. The funder had no role in study design, data collection, data analysis, data interpretation or the writing of the report. This paper also represents independent research supported by the NIHR Maudsley Biomedical Research Centre at South London and Maudsley NHS Foundation Trust and King’s College London. The views expressed are those of the author(s) and not necessarily those of the NIHR or the Department of Health and Social Care.